Digitalisasi Pelayanan Publik Dan Pengaruhnya Terhadap Kepuasan Masyarakat: Kajian Literatur Naratif - Annafi Ilham; Muhammad Rajaa Ath Thaariq; Nayla Dhea Pratiwi; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The digitalization of public services has become a strategic agenda for governance development in the Industry 4.0 era. In Indonesia, implementation of the Electronic-Based Government System (SPBE) through Presidential Regulation No. 95/2018 has driven significant bureaucratic digital transformation, evidenced by a 43-rank improvement in the UN E-Government Development Index from 107th (2018) to 64th (2024). However, the relationship between digitalization and citizen satisfaction still reveals gaps requiring deeper examination. This article narratively reviews key findings from 16 Scopus and SINTA academic articles (2019–2024) as the primary review corpus, using a narrative literature review approach that relies on thematic synthesis and critical analysis of 16 purposively selected articles. Five major themes were identified: (1) conceptualization of digital transformation, (2) e-government service quality and citizen satisfaction, (3) digital governance and co-production, (4) the Indonesian and developing country context, and (5) digital infrastructure impacts. Findings consistently demonstrate that digitalization positively influences citizen satisfaction through improved accessibility, efficiency, information quality, and system trust. The digital divide, low digital literacy, and bureaucratic resistance are critical moderators that weaken these positive effects. Four research gap dimensions are identified: contextual, methodological, thematic, and temporal, indicating the urgency of quantitative empirical research in the Indonesian context.